First report of Trypanosoma vivax infection in dairy cattle from Costa Rica - De Oliveira, Jaqueline B. (2009)
An outbreak of haemoparasitoses occurred from October 2007 to July 2008 in cattle from the district of Rio Cuarto, province of Alajuela, Costa Rica. Fifty animals of various ages out of 450 Brown Swiss were affected. The animals presented fever, severe anemia, jaundice, abortion or premature birth, loss of appetite, decrease milk production and accentuated weight loss in a short period of time. Haemoparasites were observed in the blood smears: Anaplasma marginale was present in 17 animals (60.7%); Trypanosoma vivax in nine (32.1%) and Babesia bovis in two (7.1%). Three of the animals (10.7%) had a mixed infection with T. vivax and A. marginale. After treatment, all the animals were clinically recovered and subsequent blood samplings showed no parasites. Data suggest that the outbreak might be related to a decrease in the availability and quality of the pastures due to very heavy rainfalls during the year 2007, as well as an increase in the abundance of Boophilus microplus and Stomoxys calcitrans. This is the first report of the presence of T. vivax in Costa Rica